2011
DOI: 10.1016/j.optmat.2010.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural and optoelectronic properties of BaThO3

Abstract: Structural and optoelectronic properties of BaThO3 cubic perovskite are calculated using all electrons full potential linearized augmented plane wave (FP-LAPW) method. Wide and direct band gap, 5.7 eV, of the compound predicts that it can be effectively used in UV based optoelectronic devices. Different characteristic peaks in the wide UV range emerges mainly due to the transition of electrons between valance band state O-p and conduction band states Ba-d, Ba-f, Th-f and Th-d.Comment: 20 pages and 7 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 30 publications
2
46
2
Order By: Relevance
“…They reveal much more important properties from theoretical and experimental point of view, such as ferroelectricity, superconductivity, optical and magnetic properties [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…They reveal much more important properties from theoretical and experimental point of view, such as ferroelectricity, superconductivity, optical and magnetic properties [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The study of optical properties is aimed at determining the dielectric function, refractive index, absorption coefficient, and energy loss spectroscopy of the CsSrF 3 material. Similar studies of the optoelectronic properties of some materials have been reported in the literature [14][15][16]. The present study is organized as follows: in Section 2, we briefly describe the computational details used in this work.…”
Section: Introductionmentioning
confidence: 74%
“…For k-space integration and full convergence in the irreducible Brillouin zone (IBZ), 35 k-points are used. Structural optimizations have been performed by a process of volume optimizations [43], see Fig. 2, which provides structural parameters such as lattice constant a 0 , bulk modulus B and its pressure derivative B , ground state volume V and energy E of unit cell (see Table I).…”
Section: Structural Propertiesmentioning
confidence: 99%